P1.26 Evaluation of two diagnostic systems for the detection of chlamydia trachomatis (CT) and neisseria gonorrhoeae (NG) using male urethral swabs. (8th July 2017) - Williams, James A; Ermel, Aaron; Fife, Kenneth
Abstract : Introduction: Urine is the specimen of choice for CT and NG molecular testing from males and many of the next generation testing platforms are not FDA approved for use with urethral swabs. Urethral swabs remain valuable in research settings that may require that the specimen is collected in a manner preserving organism viability. The goal of this study was to assess the Abbott m 2000 Realtime ( m 2000), and Roche COBAS 4800 (c4800) systems for the identification of CT and NG in urethral swabs collected in chlamydia transport medium (CTM). Methods: Archived male urethral swabs collected in CTM from STD clinic attendees were tested. These specimens were originally tested for CT and NG on a platform FDA-approved for urethral swabs collected in CTM (Roche COBAS Amplicor, (cAMP)).Two-hundred µl of CTM was added into each manufacturer's collection device. This was subsequently tested on the m 2000 and c4800 systems according to the manufacturer's instructions. CT and NG results obtained from each platform were compared to the original cAMP results to determine sensitivity and specificity. Agreement between platforms was measured by calculating the kappa coefficient. Results: One hundred urethral swab specimens were available for testing (28 CT and 25 NG positives). When compared to results obtained with the cAMP, the sensitivity and specificity of the m 2000 for the detection of CT was 100% and 98.6%, respectively; the sensitivity and specificity on the c4800 was 96.4% and 98.6%. For NG, the sensitivity and specificity of the m 2000 assay was 100% and 98.7%; the c4800 assay was 100% sensitive and specific. Agreement was excellent for both platforms when compared to cAMP with kappa scores of >0.95 for CT and >0.97 for NG. Conclusion: The m 2000 and c4800 platforms have similar performance characteristics to cAMP for the detection of CT and NG using urethral swabs in CTM. This study will provide investigators with additional options when designing protocols that require the preservation and ability to recover viable organisms from men.